Codification of customary practice for promoting Muslim women’s right to land and property: a case study of the harta sepencarian rule in Malaysia - Maidin, Ainul Jaria (Serials Publications, 2014)
Protecting women’s rights to property is an important aspect in promoting sustainable development, an agenda being championed by governments both at national and international level including the Non-governmental organisations (NGOs) throughout the world. This chapter seeks to set out the development in Malaysia where the Adat Perpatih practices have been incorporated into the Syariah Enactments to promote protection of property rights of women on divorce. The customary practice that is the focus of this chapter is the practice of dividing jointly acquired matrimonial property (harta sepencarian) during the subsistence of a marriage where the women is assured her rightful share upon divorce or on the death of the spouse. This case study is presented to provide a useful model for the Muslims and others to develop their customary practices which may promote access to property rights for women to overcome the shortcomings in the legal system.